Botanic Garden - (:unkn) unknown (Waterman the Hatter, Clothier and Outfitter, Trinidad, 2009)
A tall tree looms over a park bench is one of many places in the Botanical Gardens where visitors can enjoy the tranquillity.
Colour: Coloured; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Botanical gardens--Trinidad and Tobago; Trees--Trinidad and Tobago; Plants--Trinidad and Tobago; Benches--Trinidad and Tobago; Garden ornaments and furniture--Trinidad and Tobago